Organising football matches with spectators during the COVID-19 pandemic: What can we learn from the Amir Cup Football Final of Qatar 2020? A call for action - Dergaa, Ismail; Varma, Amit; Tabben, Montassar; Ali Malik, Rubena; Sheik, Sanaulla; Vedasalam, Sakthikumar; Khellil Abbassi, Ahmed; Almulla, Jassim; Chaabane, Mokhtar; Chamari, Karim (Biology of Sport, 2021)
The COVID-19 pandemic is a potential threat to professional sporting events when they eventually return to their usual calendar with spectators’ capacity of football stadiums usually exceeding 40,000 seats for important events. Hence, a strategy for safe return to sporting events is needed in the COVID-19 pandemic to pave the way towards a new normalcy. We reviewed the guidelines and policies implemented in organising the Amir Cup Football Final of Qatar, which hosted about 20,000 fans. The authors evaluated the publicly available information on the official websites of the various organizations involved and highlight the importance and usefulness of the Covid-19 Rapid Antigen Assay-Kit as a tool for screening sports spectators as well as the importance of a rigorous spectator pathway, including their accurate traceability thanks to a specific mobile phone application. Despite the surging of COVID-19 all over the world, a big football event with around 20,000 spectators in the same stadium has been hosted under strongly controlled preventative measures. These preventative measures show that it is possible to organize a major football match held outdoors, with the presence of thousands of supporters. This article is a call for action for the organisers of such events where the supporters’ health status is traceable to provide the scientific community with actual data of post-event infection rates. Therefore, it is suggested to consider using procedures like the ones described in the present article as a potential model in the process of organizing big sporting events with spectators in times of COVID-19.